The impact of training based on the transtheoretical model on increasing physical activity in overweight and obese housewives - Tayebeh Rakhshani; Zahra Jalalpour; Mohsen Jafari; Samira Taravatmanesh; Amirhossein Kamyab; Ali Khani Jeihooni (BMC Women's Health)
Abstract Background Due to the nature of their activities, housewives are often at higher risk of weight gain. Considering the importance of interventions and the role of housewives in the family, the present study was designed and conducted to examine the impact of training based on the Transtheoretical Model on increasing physical activity in overweight and obese housewives. Methods This quasi-experimental study was conducted on 120 overweight and obese housewives attending comprehensive health centers in Yazd, Iran. The sampling method was multi stage, and participants were randomly assigned to two groups: intervention (60 participants) and control (60 participants). The educational intervention consisted of six 90-minute sessions held over one and a half months (one session per week) in person. The educational content provided to the intervention group was based on the Transtheoretical Model. Data collection tools included standardized physical activity and behavior change questionnaires based on the Transtheoretical Model, Data were analyzed using SPSS version 27 with paired t-tests, independent t-tests, and chi-square tests. Results Independent t-test results showed after the intervention, the differences between two group were statistically significant (P = 0.001). Additionally, independent t-test results showed no significant difference in physical activity levels between the intervention and control groups before the educational intervention (P = 0.312), whereas the difference became statistically significant after the intervention (P = 0.001). Conclusion The findings of this intervention demonstrated that interventions based on the Transtheoretical Model effectively improve behavior, identify barriers and benefits of physical activity, and enhance self-efficacy in overweight and obese housewives. This study revealed that the Transtheoretical Model, through identifying perceived barriers and benefits (via the training provided) and, most importantly, improving self-efficacy and behavior, led to an increase in physical activity among housewives.